Conference Realignment and TV: The Correlation Between the Two Since 1977, and Their Impact on College Basketball's Competitive Balance Today - Kotlarik, Kris (My University, 2013)
Beginning in the summer of 2010, a series of moves shook the landscape of Division I college sports. These moves were primarily centered around football (and the revenue generated by football). During this wave of realignment, geography and tradition were thrown by the wayside as conferences like the Big 12 and Big East became misnomers. Rivalries across the country were disrupted. Behind the scenes of football powerhouses trying to gain a step on each other, the sport of college basketball was also shaken up by these moves. Realignment has always occurred in college sports; however, as each cycle of realignment occurs, the connection television money and football has become more prevalent. This paper will trace the origin and evolution of television in college sports, and the impact of television on past realignments, using a mix of primary and secondary sources, the latter focusing on the patterns of the NCAA between the 1950s and the mid-1980's. This paper will also examine the impact of the latest wave of realignment on college basketball with respect to rivalries and conferences, with a heavy use of primary sources, particularly newspapers and other online coverage.
Keywords: Basketball--United States--History--20th century; College sports--United States--History--20th century; College sports--United States--Management; College sports--Economic aspects--United States